PENGARUH PROFITABILITAS, DIVIDEN, LEVERAGE, DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN - Arif Irfandani; Metta Kusumaningtyas; Yohana Kus Suparwati (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2017)
Firm value are certain conditions that have been achieved by a company as a description of public confidence in the company after going through a process of activities for several years, namely since the company was founded until now. This study aims to examine and analyze the effect of profitability, dividends, leverage, and corporate social responsibility to corporate value empirical study on companies listed in the Indonesia Stock Exchange. The sampling technique in this research is using purposive sampling method. The analytical method used is multiple linear regression. The analysis showed that the positive effect on the profitability of the variable value of the company, dividends positive effect on the value of the company, while leverage has no effect on the value of the company and corporate social responsibility variable does not affect the value of the company. Adjusted R2 value of this research model is 49.3%.